2019
DOI: 10.1093/ejcts/ezz064
|View full text |Cite
|
Sign up to set email alerts
|

Cost–utility analysis of minimally invasive surgery for lung cancer: a randomized controlled trial

Abstract: OBJECTIVES: Minimally invasive video-assisted thoracic surgery (VATS) was first introduced in the early 1990s. For decades, numerous non-randomized studies demonstrated advantages of VATS over thoracotomy with lower morbidity and shorter hospital stay, but only recently did a randomized trial document that VATS results in lower pain scores and better quality of life. Opposing arguments for VATS have always been increased costs and concerns about oncological adequacy. In this paper, we aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…For stages I-II, the pooled HSUV was 0.78 (95% CI 0.70-0.86) across 1510 individuals. There was significant heterogeneity across stage I-II studies (p < 0.01; I 2 = 92%), as results ranged from 0.62 (95% CI 0.51-0.72) [40] to 0.88 (95% CI 0.86-0.90) [47]. The pooled HSUV for stage III-IV was 0.69 (95% CI 0.65-0.73) across 4703 individuals.…”
Section: Study Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…For stages I-II, the pooled HSUV was 0.78 (95% CI 0.70-0.86) across 1510 individuals. There was significant heterogeneity across stage I-II studies (p < 0.01; I 2 = 92%), as results ranged from 0.62 (95% CI 0.51-0.72) [40] to 0.88 (95% CI 0.86-0.90) [47]. The pooled HSUV for stage III-IV was 0.69 (95% CI 0.65-0.73) across 4703 individuals.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Among the included studies, the number of patients included for HSUV analysis ranged from 43 to 2396. Only two of 27 studies clearly stated that missing HRQoL data were imputed or that HRQoL response was complete [37,47]. Six studies performed multiple HRQoL measurements in the same participants.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Nevertheless, these authors reported a significantly lower cost of their minimally invasive techniques compared to the mean cost in France (P = 0.001). Conversely, VATS was found to be a cost-effective alternative compared to thoracotomy in the randomized controlled trial of Bendixen et al [47] , with a savings of €4267 (P < 0.001). Subramanian et al [48] reported that, compared to open lobectomy, RATS lobectomy was 13% more expensive (P < 0.001) and VATS lobectomy 2% less expensive (P = 0.007).…”
Section: Discussionmentioning
confidence: 93%
“…-Most of the operations were performed using VATS. The minor incidence of the post-thoracotomy pain especially in the early postoperative period has been recently reported in a large randomized trial comparing the two surgical approaches (28).…”
Section: Limitationsmentioning
confidence: 93%